Dynamic off-resonance correction improves functional image analysis in fMRI of awake behaving non-human primates - Shahdloo, Mo; Khalighinejad, Nima; Priestley, Luke; Rushworth, Matthew; Chiew, Mark (Frontiers in Neuroimaging, 2024)
Use of functional MRI in awake non-human primate (NHPs) has recently increased. Scanning animals while awake makes data collection possible in the absence of anaesthetic modulation and with an extended range of possible experimental designs. Robust awake NHP imaging however is challenging due to the strong artifacts caused by time-varying off-resonance changes introduced by the animal's body motion. Recently, an image reconstruction technique has been proposed to estimate these off-resonance changes using the navigator data that is typically collected during fMRI scans to correct the data and compensate for the changes. In this study, we sought to thoroughly investigate the effect of this correction on the brain activation estimates using extended awake NHP data. Our results show significant improvements in image fidelity using our proposed correction strategy, as well as greatly enhanced and more reliable activation estimates in GLM analyses.